Quality and Consumer Acceptability of Santol Candy, Kamias and Balimbing Prunes - Emma Ruth Bayogan; Anne Catherine Padilla (Davao Research Journal)
This study aimed to determine some physico-chemical characteristics of santol candy, kamias prunes and balimbing prunes; as well as the microbial safety of these dehydrated fruits, and; know the consumer's acceptability of these processed fruits in Mati, Davao Oriental. Santol was plumped for 1, 2, 3 and 4 weeks which served as treatments. These dehydrated fruits were also stored at ambient for about four months for santol and three months for kamias and balimbing. The data gathered were % moisture content, total soluble solids (TSS), % titratable acidity (TA), pH, total plate count (TPC), yeast and mold count (YMC) and consumer preference. Moisture content for santol candy generally increased towards the second month of storage although there was again a decrease on the fourth month. TSS of santol candy generally decreased over time. A significant difference for % Tawas noticeable during the first two months of storage, and on the last two months, results did not vary significantly on all treatments. Significant differences on the pH between treatments were seen before and after four months of storage. An increasing trend in TPC and YMC was noticeable during the 4-month storage at ambient.